(untitled) (Vietnam Journal of Community Medicine, 2024)
Research objective: The study was conducted to evaluate the effectiveness of music therapy on patient anxiety during the procedure and determine some factors related to patient anxiety scores before and after the procedure. Research methods: The randomized controlled experimental study was conducted on 120 patients undergoing the procedures at the Endovascular Intervention Unit of the Ho Chi Minh city University of Medicine and Pharmacy Hospital, Vietnam. Patients will be divided into two groups; one group will receive music during the procedure and the other will not. The testing period is from March 2024 to May 2024. Results: The level of anxiety and anxiety scores in the group of patients listening to music changed before and after intervention, and the change was statistically significant with p < 0.05. Before intervention, anxiety scores according to the STAI scale between the 2 groups did not have a statistically significant difference (p = 0.87). However, the anxiety scores according to STAI between the 2 groups after intervention had a statistically significant difference with p = 0.04. The intervention group decreased 5.63 points and the control group decreased 1.23 points after intervention, and this change was statistically significant with p < 0.001. There is a relationship between age group, working status, and listening to music during the procedure with patients’ anxiety scores before and after the music intervention. Older, non-working people who did not listen to music during the procedure had higher anxiety scores than the other groups. Conclusion: Music effectively reduces patient anxiety during the procedure.